Three years of growth hormone treatment in young adults with Prader-Willi syndrome: sustained positive effects on body composition - Damen, Layla; Donze, Stephany H.; Kuppens, Renske J.; Bakker, Nienke E.; de Graaff, Laura C. G.; van der Velden, Janielle A. E. M.; Hokken-Koelega, Anita C. S. (Orphanet journal of rare diseases, 2020)
Background In children with Prader-Willi syndrome (PWS), the benefits of growth hormone treatment are well established. Several one-year studies have shown that growth hormone is also beneficial for adults with PWS, improving body composition. However, little is known about the longer-term effects. This study investigated the effects on body composition in adult patients with PWS during 3 years of growth hormone therapy in a dose of 0.33 mg/m 2 /day. Methods Open-label, prospective study in 43 young adults with PWS with a median (IQR) age of 19.0 (17.5 to 20.7) years. Fat mass percentage SDS and lean body mass SDS were measured annually by DXA. Results Estimated mean (95% CI) fat mass percentage SDS decreased during the three-year study from 2.1 (1.9 to 2.3) SDS at start to 1.9 (1.8 to 2.1) SDS, p = 0.012, while lean body mass SDS remained stable at − 2.1 (− 2.4 to − 1.8) SDS at start to − 1.9 (− 2.3 to − 1.6) after 3 years, p = 0.15. Fasting glucose and insulin remained similar during the three-year study, glucose being 4.6 (4.4 to 4.8) mmol/l at start and 4.6 (4.5 to 4.7) mmol/l after 3 years of growth hormone, p = 0.93 and insulin being 59.5 (42.2 to 81.5) pmol/l and 55.0 (42.4 to 69.2) pmol/l, resp., p = 0.54. There were no growth hormone-related adverse events during the study. Conclusions Three years of growth hormone treatment in young adults with PWS maintains the positive effects on body composition attained during childhood. Thus, adults with PWS benefit from longer-term growth hormone treatment. Trial registration EudraCT, EudraCT number 2011-001313-14 . Registered 17 October 2012.